Analisis Sentimen Public Program Makan Bergizi Gratis Platform Instagram Dengan Algoritma SVM - Wardianto; Muhamad Jakak, Pamuji; Rohman, Miftakhul (Universitas PGRI Kanjuruhan Malang, 2025)
Public sentiment towards the Free Nutritious Meal Program on the Instagram social media platform is the subject of this study. Using the Support Vector Machine (SVM) algorithm, we classify sentiment from Instagram user reviews into positive, negative, and neutral categories. The SVM algorithm demonstrates a strong performance, with an accuracy of 0.90 in classifying sentiment. Moreover, the sentiment analysis reveals that most public reactions are neutral towards this program. This study has the potential to significantly influence decision-making by providing insights into how the public views government programs and the importance of considering sentiment.